A Survey of 2D and 3D Image Matching in Industrial Object Alignment. Issue 3 (2nd July 2016) - Chen, Chin-Sheng; Huang, Chien-Liang; Yeh, Chun-Wei
Abstract: Image matching is a practical tool in the computer vision domain. 2D and 3D image matching can be based on (2D) features or on view and point (3D) which can be cloud based. Intensive practical research has been done on both 2D and 3D image matching and the methods are generally designed to meet the requirements of industrial alignment applications and include such aspects as full rotation, scaling and the handling of multiple objects. The aim of this study is the presentation of a review of 2D and 3D image matching and the provision of a comprehensive reference source for those involved in image matching. Graphical abstract: